Liver Cancer - Lasfar, Ahmed (IntechOpen, 2018)
This book offers remarkable coverage of liver cancer from etiology to prevention and treatment. It provides an updated and new vision of this major cancer that continues to affect hundreds of thousands of people and remains one of the leading causes of cancer deaths around the world. To ensure the high quality of this book, important insights are included and rigorously discussed in a simple and authentic way. The book includes detailed and updated descriptions of the main causes of liver cancer and also the prevention and treatment of this disease. This book is a relevant source of knowledge, very useful for researchers, medical doctors, medical residents, students, healthcare providers, public health decision makers, and all individuals interested in the prevention of this disease.